A Review of Self‐Healing Concrete for Damage Management of Structures. Issue 17 (16th May 2018) - De Belie, Nele; Gruyaert, Elke; Al‐Tabbaa, Abir; Antonaci, Paola; Baera, Cornelia; Bajare, Diana; Darquennes, Aveline; Davies, Robert; Ferrara, Liberato; Jefferson, Tony; Litina, Chrysoula; Miljevic, Bojan; et al.
Abstract: The increasing concern for safety and sustainability of structures is calling for the development of smart self‐healing materials and preventive repair methods. The appearance of small cracks (<300 µm in width) in concrete is almost unavoidable, not necessarily causing a risk of collapse for the structure, but surely impairing its functionality, accelerating its degradation, and diminishing its service life and sustainability. This review provides the state‐of‐the‐art of recent developments of self‐healing concrete, covering autogenous or intrinsic healing of traditional concrete followed by stimulated autogenous healing via use of mineral additives, crystalline admixtures or (superabsorbent) polymers, and subsequently autonomous self‐healing mechanisms, i.e. via, application of micro‐, macro‐, or vascular encapsulated polymers, minerals, or bacteria. The (stimulated) autogenous mechanisms are generally limited to healing crack widths of about 100–150 µm. In contrast, most autonomous self‐healing mechanisms can heal cracks of 300 µm, even sometimes up to more than 1 mm, and usually act faster. After explaining the basic concept for each self‐healing technique, the most recent advances are collected, explaining the progress and current limitations, to provide insights toward the future developments. This review addresses the research needs required to remove hindrances that limit market penetration of self‐healing concrete technologies. Abstract : Self‐healing concrete is a smart concrete designed to manage occurring cracks through the activation of an incorporated mechanism resulting in autonomous healing of cracks. This damage management principle provides the material superior functionality with respect to reduced maintenance and repair requirements, increased service life, and sustainability. This review article elucidates and critically evaluates different (stimulated) autogenous and autonomous healing mechanisms.